Design, synthesis, and biological evaluation of 6-methoxy-2-arylquinolines as potential P-glycoprotein inhibitors - Aboutorabzadeh, Sayyed Mohammad (Iran J Basic Med Sci, 2018)
OBJECTIVE(S): In the present study, a new series of 6-methoxy-2-arylquinoline analogues was designed and synthesized as P-glycoprotein (P-gp) inhibitors using quinine and flavones as the lead compounds. MATERIALS AND METHODS: The cytotoxic activity of the synthesized compounds was evaluated against two human cancer cell lines including EPG85-257RDB, multidrug-resistant gastric carcinoma cells (P-gp-positive gastric carcinoma cell line), and EPG85-257P, drug-sensitive gastric carcinoma cells. Compounds showing low to moderate toxicity in the MTT test were selected to investigate their P-gp inhibition activity. Moreover, trying to explain the results of biological experiments, docking studies of the selected compounds into the homology-modeled human P-gp, were carried out. The physicochemical and ADME properties of the compounds as drug candidate were also predicted. RESULTS: Most of our compounds exhibited negligible or much lower cytotoxic effect in both cancer cells. Among the series, 5a and 5b, alcoholic quinoline derivatives were found to inhibit the efflux of rhodamine 123 at the concentration of 10 μM significantly. CONCLUSION: Among the tested quinolines, 5a and 5b showed the most potent P-gp inhibitory activity in the series and were 1.3-fold and 2.1-fold stronger than verapamil, respectively. SAR data revealed that hydroxyl methyl in position 4 of quinolines has a key role in P-gp efflux inhibition of our compounds. ADME studies suggested that all of the compounds included in this study may have a good human intestinal absorption.